X-ray structural insights and computational analysis of the compound 5-ethyl-4-[(4-morpholinobenzylidene)amino]-2,4-dihydro-3H-1,2,4-triazole-3-thione - Syed Nizamuddin; T. N. Mahadeva Prasad; N. R. Sreenatha; C. L. Sharath; B. N. Lakshminarayana; K. A. Vishnumurthy (Acta Crystallographica Section E: Crystallographic Communications)
The title compound, C15H19N5OS, crystallizes in the monoclinic crystal system, space group P21/c. The molecule adopts a non-planar geometry. A significant feature of the structure is the puckered six-membered morpholine ring, which adopts a chair conformation. In the crystal, molecules are linked through intermolecular N—H...S hydrogen bonds, forming inversion-related dimers with an R22(8) ring motif. A Hirshfeld surface analysis was undertaken to quantify the intermolecular interactions that influence the crystal packing.